Quantum computer error structure probed by quantum error correction syndrome measurements - Spiro Gicev; Lloyd C. L. Hollenberg; Muhammad Usman (Physical Review Research, 2024)
With quantum devices rapidly approaching qualities and scales needed for fault tolerance, the validity of simplified error models underpinning the study of quantum error correction needs to be experimentally evaluated. In this work, we have assessed the performance of IBM superconducting quantum computer devices implementing heavy-hexagon code syndrome measurements with circuit sizes up to 23 qubits, against the error assumptions underpinning code threshold calculations. Circuit operator change rate statistics in the presence of depolarizing and biased noise were modeled using analytic functions of error model parameters. Data from 16 repeated syndrome measurement cycles were found to be inconsistent with a uniform depolarizing noise model, with slightly improved fits found with biased and inhomogeneous noise models. Spatial-temporal correlations investigated via Z stabilizer measurements revealed significant temporal correlation in detection events. These results highlight the nontrivial structure that may be present in the noise of quantum error correction circuits, revealed by operator measurement statistics, and support the development of noise-tailored codes and decoders to adapt.